Crystal Structures of Enterovirus 71 3C Protease Complexed with Rupintrivir Reveal the Roles of Catalytically Important Residues - Wang, Jing (American Society for Microbiology, 2011)
EV71 is the primary pathogenic cause of hand-foot-mouth disease (HFMD), but an effective antiviral drug currently is unavailable. Rupintrivir, an inhibitor against human rhinovirus (HRV), has potent antiviral activities against EV71. We determined the high-resolution crystal structures of the EV71 3C(pro)/rupintrivir complex, showing that although rupintrivir interacts with EV71 3C(pro) similarly to HRV 3C(pro), the C terminus of the inhibitor cannot accommodate the leaving-group pockets of EV71 3C(pro). Our structures reveal that EV71 3C(pro) possesses a surface-recessive S2′ pocket that is not present in HRV 3C(pro) that contributes to the additional substrate binding affinity. Combined with mutagenic studies, we demonstrated that catalytic Glu71 is irreplaceable for maintaining the overall architecture of the active site and, most importantly, the productive conformation of catalytic His40. We discovered the role of a previously uncharacterized residue, Arg39 of EV71 3C(pro), that can neutralize the negative charge of Glu71, which may subsequently assist deprotonation of His40 during proteolysis.